Roadmap on magnetoelectric materials and devices - Liang, X. (2021)
The possibility of tuning the magnetic properties of materials with voltage (converse magnetoelectricity) or generating electric voltage with magnetic fields (direct magnetoelectricity) has opened new avenues in a large variety of technological fields, ranging from information technologies to healthcare devices and including a great number of multifunctional integrated systems, such as mechanical antennas, magnetometers, and radio frequency (RF) tunable inductors, which have been realized due to the strong strain-mediated magnetoelectric (ME) coupling found in ME composites. The development of single-phase multiferroic materials (which exhibit simultaneous ferroelectric and ferromagnetic or antiferromagnetic orders), multiferroic heterostructures, as well as progress in other ME mechanisms, such as electrostatic surface charging or magneto-ionics (voltage-driven ion migration), have a large potential to boost energy efficiency in spintronics and magnetic actuators. This article focuses on existing ME materials and devices and reviews the state of the art in their performance. The most recent progress on different ME devices based on ME heterostructures is presented but with a larger emphasis on ME antennas and sensors due to the significant advances achieved in these applications. The rapid development of mechanically actuated ME antennas has been observed over the past several years, producing ME antennas that are miniaturized by 1-2 orders compared to conventional antenna size. Magnetic sensors based on simple ME composites are potentially promising alternatives to conventional magnetometers due to their very good detectivity (<; pT/Hz 1/2 ) at low frequencies. Other ME devices reviewed in this article include RF tunable inductors with high inductance tunability and quality (Q) factor; non-reciprocal microelectromechanical system (MEMS) bandpass filters with dual H- and E-field tunability; passive isolators and gyrators in the low-frequency (LF) range; and ME random access memories for low-power data storage. All these compact and lightweight ME devices are also promising for future biomedical and wireless applications. Finally, some open questions and future directions where the community might be headed are provided.